Knowledge and Awareness Level of Contact-lens Complications in the Population of Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2025)
Contact lenses (CLs) are widely used ophthalmic devices that offer numerous benefits, such asimproved cosmesis, expanded visual field, and enhanced vision without the drawbacks associated with spectacles.However, improper use of CLs can lead to complications, including corneal abrasions, ulcers, conjunctivitis,and keratitis, with severe cases resulting in blindness due to microbial keratitis and endophthalmitis. Despite theadvantages, misuse of CLs due to a lack of knowledge and non-prescription acquisition poses significant risks tousers. Objectives: This study aims to assess the level of knowledge regarding CL complications among the SaudiArabian population and to identify the gaps in knowledge that may contribute to the misuse of CLs. Methods: A crosssectionalstudy was conducted from July 2024 to March 2025 across various regions in Saudi Arabia. A total of 386adult Saudi citizens, selected through a simple random sampling method, participated. Data were collected using avalidated, self-administered online survey comprising sociodemographic information and knowledge assessmentquestions about CL use, its complications, and factors that increase the risk of developing complications. The surveyinstrument was pilot-tested with 20 individuals to ensure clarity and feasibility. Data analysis was performed usingstatistical software to evaluate the level of knowledge and identify significant associations between sociodemographicvariables and knowledge levels. Results: This study assessed knowledge and awareness of CL complications amongthe Saudi Arabian population. Among 386 participants, 62.7% had high knowledge, 16.6% moderate, and 20.7% lowknowledge, despite 48.7% showing high awareness. Women and employment had significantly higher knowledgelevels (P < 0.05), while other sociodemographic factors were not statistically significant. Key misconceptionsincluded misunderstanding CL hygiene and risk factors. The findings highlight critical knowledge gaps despiteawareness, emphasizing the need for targeted educational interventions to improve CL safety and reduce preventablecomplications through public health campaigns and optometric counseling in Saudi Arabia. Conclusion: Thefindings of this study highlight significant gaps in knowledge and awareness regarding CL complications among theSaudi population. Despite a relatively high level of awareness, the lack of understanding concerning specific riskfactors and proper care practices poses a risk for increased complications.